Knee meniscal retears after repair: A systematic review comparing diagnostic imaging modalities. Issue 1 (31st December 2022) - Syed, Saad; Nagdi Zaki, Mohammed; Lakshmanan, Jeyaseelan; Kundra, Rik
ABSTRACT: The meniscus is a relatively avascular fibrocartilaginous structure that provides a key role in shock absorption and load transmission. However, accurate diagnosis of meniscal retear can present a clinical challenge. The purpose of this study was to conduct a systematic review on the available literature, which compare the sensitivities, specificities, and accuracies of different diagnostic modalities of diagnosing knee meniscal retears in patients who have undergone surgical meniscal repair, such as Magnetic Resonance Imaging (MRI), Magnetic Resonance Arthrography with intraarticular contrast (direct MRA), and a combination of MRI and direct MRA. Two authors independently searched two databases (PubMed and Scopus) for literature related to knee meniscus retear according to the PRISMA guidelines. Four studies were found, which resulted in 291 patients with 293 menisci. All studies were published in 2008 and 2014. In our analysis, we calculated sensitivity to be 78.79% (95% CI, 64.07–93.51), specificity to be 56.58% (95% CI, 20.21–92.94), and overall accuracy to be 66.25% (95% CI, 54.29–78.22) for MRI and sensitivity to be 87.84% (95% CI, 83.93–91.74), specificity to be 88.68% (95% CI, 81.93–95.43), and overall accuracy to be 87.22% (95% CI, 82.22–91.62) for direct MRA. We recommend the use of direct MRA for the diagnosis of meniscal retears due to its higher sensitivity, specificity, and accuracy as compared to MRI and its reduced cost and invasive nature as compared to second-look arthroscopy. However, our review is limited by the number of studies available on this topic. More studies using study designs such as randomized controlled trials, involving MRI, direct MRA, and combinations of such techniques, should be performed to accurately assess the different techniques and aid in designing guidelines to guide the diagnosis of meniscal retears following meniscal repair.